Por Que Ensinar Desenho No Curso Primário? Um Estudo Sobre As Suas Finalidades (1829- 1950) - Guimaraes, Marcos Denilson [UNIFESP] (2017)
This thesis has as a main objective to analyze, in a historical perspective, which changes the purposes of teaching Drawing in primary school from 1829 to 1950 have gone through. It was adopted the chronological landmark, regarding the year of the first manual found for the teaching of Drawing and the year of publication of São Paulo’s programs in 1949 and 1950, where the subject of Drawing was present. The sources that have been studied are official teaching documents: laws, decrees, decisions, programs, reports, manuals and pedagogical magazines. Analyzing the changes of Drawing purposes implied in searching to understand the reason to make Drawing as a subject of the primary school. Thus, this investigation was based mainly on the studies of Chervel (1990), in order to comprehend the school purposes; the studies of Trouvé (2008, 2010), on the conception of the elementary/rudimentary pair and in the theoretical and methodological assumptions from Chartier’s (1990) cultural history. The sources analyses have permitted to identify different purposes attributed to the teaching of Drawing, which have changed throughout time. Amongst stays and ruptures, the Drawing teaching in primary school has been a fruit of a complex process, notably marked by the appropriation of discourses. It was observed that, in the first analyzed period (first and second halves of the 19th century), the teaching of Drawing had as the main objective to develop the manual and visual skills, in order to educate the eyes and to make the hand steady, so that the students would be able to construct the geometric figures and further works. Hence, in the form of elements, it served as a way of access to more elaborated knowledges. The learning of these abstract and theoretical concepts was linked to a special kind of advanced knowledge, entitled Euclidian geometry. Considered as rudiments (the first half of the 20th century), when it gained autonomy in relation to geometry, the Drawing teaching started to be seen as a way of preparing children for future professions, developing their intellectual faculties, promoting the observation, educating the judgement and developing the esthetic sense.